Between Compliance and Commitment: A Temporal Critical Discourse Analysis of How National and International Oil Companies Respond to Evolving Climate-Related ESG Regulations in Their Public Disclosures, 2016–2026 - Nugroho Nugroho; Rahmatul Husni (Riviera Publishing, 2026)
Over the decade from the Paris Agreement to the EU Omnibus I deregulation, the regulatory landscape for corporate climate disclosure has shifted from voluntary frameworks toward mandatory reporting, before partially reversing. Yet how National Oil Companies (NOCs) and International Oil Companies (IOCs) have responded to these evolving demands remains underexplored. This research employed longitudinal hybrid Critical Discourse Analysis and thematic content analysis on 176 reports from sixteen NOCs and IOCs across four regions (2016–2026 Q1). Guided by regulatory-response theory, legitimacy theory, and institutional logics, it examines how NOC and IOC disclosures diverged or converged in response to successive regulatory regimes and what discursive strategies were employed. Findings reveal three key patterns. First, European IOCs rapidly adopted TCFD/ISSB frameworks, with